2022
DOI: 10.3233/bmr-210110
|View full text |Cite
|
Sign up to set email alerts
|

The combined treatment of entrapped Infrapatellar Branch of the Saphenous Nerve after ACL reconstruction: Ultrasound-guided perineural injection and acupotomy

Abstract: BACKGROUND: The anterior cruciate ligament (ACL) reconstruction (ACLR) under the arthroscopy is a widespread procedure for ACL rupture, which could stabilize knee and promote recovery. However, one of its complications is the injury of infrapatellar branch of saphenous nerve (IBSN). In traditional Chinese medicine, acupotomy functions via releasing and stripping adhesion tissues. Accordingly, acupotomy is suitable for the treatment of entrapped nerve injury and tissues adhesion. CASE DESCRIPTION: A 14-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Rao et al. [ 13 ] suggested that ultrasound-guided acupotomy combined with peripheral nerve block represents a new method for treating saphenous nerve entrapment in the knee joint, with relatively long-lasting effects. Choi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rao et al. [ 13 ] suggested that ultrasound-guided acupotomy combined with peripheral nerve block represents a new method for treating saphenous nerve entrapment in the knee joint, with relatively long-lasting effects. Choi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the potential of combining X-ray or ultrasound-based SNRB with acupotomy to treat lumbar disc herniation and entrapment of the inferior patellar branch of the saphenous nerve [ 12 , 13 ]. However, there is no report on whether this combination of treatments could be used to treat CSR.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in order to meet some specific goals, some acupuncture needles with particular structure also have been reported. For example, the acupotomy, the combination of needle and knife, can release and strip adhesion structures or soft tissues through the little knife at the tip of the needle [172].…”
Section: Millineedles For Acupuncturementioning
confidence: 99%